2020
DOI: 10.1002/jrs.6002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of total iron‐binding capacity of transferrin using metal organic framework‐based surface‐enhanced Raman scattering spectroscopy

Abstract: We report the rapid and sensitive determination of the total iron‐binding capacity of transferrin (Tf) in human serum using surface‐enhanced Raman scattering (SERS) spectroscopy. Herein, metal organic framework (MOF)–gold nanoparticle (AuNP) complexes were used as the SERS substrate. The highly porous MOF preconcentrates the reporter molecules and accelerates the approach of the reporter molecules to the vicinity of the AuNPs on the surface of the MOF. As a result, a significant number of reporter molecules ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…This led to the creation of a SERS sensing platform that could detect FA in biological samples. The research team has also synthesized many SERS substrates with PNPs anchored on MOF surfaces, including AuNPs/Cu-TCPP, 62 AgNPs@MOF helical structure, 63 AuNPs@MB@HP-UiO-66-NH2, 64 TM-Ag@NU-901, 65 AuNPs@MOFs, 66,67 and Ag@MIL-101(Cr). 68 Despite the significant progress made in anchoring PNPs to MOF surfaces as SERS substrates, there are still some challenges that need to be addressed.…”
Section: Ship-on-a-bottle Strategymentioning
confidence: 99%
“…This led to the creation of a SERS sensing platform that could detect FA in biological samples. The research team has also synthesized many SERS substrates with PNPs anchored on MOF surfaces, including AuNPs/Cu-TCPP, 62 AgNPs@MOF helical structure, 63 AuNPs@MB@HP-UiO-66-NH2, 64 TM-Ag@NU-901, 65 AuNPs@MOFs, 66,67 and Ag@MIL-101(Cr). 68 Despite the significant progress made in anchoring PNPs to MOF surfaces as SERS substrates, there are still some challenges that need to be addressed.…”
Section: Ship-on-a-bottle Strategymentioning
confidence: 99%
“…Since then, an exponentially growing interest has been focused on improving the SERS substrates to enhance the performance of the technique but also to implement these structures in the point-of-care (PoC) devices. In the last few years, hybrid compounds composed of bidimensional nanomaterial have been exploited with an increasing frequency as SERS substrate [32], but also, other types of composites have been exploited, such as for example metal-organic framework (MOF)-gold nanoparticle (AuNPs) complexes [33].…”
Section: Localized Surface Plasmon Resonances (Lspr)mentioning
confidence: 99%
“…Various particles, such as gold nanoparticles (AuNPs), have been increasingly employed in the development of lateral flow test strips for their unique optical, electronic, and/or structural properties. For example, Das et al reported a rapid and sensitive determination of the total iron-binding capacity of transferrin (Tf) in human serum using surface-enhanced Raman scattering (SERS) spectroscopy [46]. In the study, metal organic framework (MOF)-gold nanoparticle (AuNP) complexes were used as the SERS substrate.…”
Section: Immunoassay Paper-based Devices/technologymentioning
confidence: 99%